Functional foods : concept to product - Gibson, Glenn R.; Williams, Christine M. (Woodhead Publishing in food science and technology, 2000)
Functional Foods are widely predicted to become one of the biggest dietary trends of the next twenty-five years. This book first defines and classifies the field of functional foods, paying particular attention to the legislative aspects in both the US and Europe. It then summarises the key work on functional foods and the prevention of disease. Finally there are a series of chapters on the issues in developing functional foods in practice.